ANALYSIS OF THE ROLE OF TRANSFER PRICING AND EARNING MANAGEMENT IN TAX AVOIDANCE IN INDONESIAN COMPANIES Yuki Elvira1, Sari Dewi2 - Sari Dewi; Yuki Elvira (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Indonesia is a country that cannot be separated from the problem of tax avoidance. Each country has different corporate income tax rates, for example, Indonesian and Japanese tax rates, where the Indonesian tax rate charged to entities is 25% and the Japanese tax rate charged to entities is 23%. It can be seen that Japan's tax rate is lower than Indonesia, therefore there are many companies that want to do tax avoidance. This research is basic research to solve the problem theoretically and is expected to support further theory development. This study examines the effect of independent variables consisting of transfer pricing and earnings management on tax avoidance as the dependent variable. The control variables used in this study are profitability, leverage, tangibility, liquidity, age, and company size. This study uses data from non-financial sector companies that have been audited and published on the official website of the Indonesia Stock Exchange (IDX). Time data collection methods used in this study arecross-sectionall and time series. The research data sample was obtained through a purposive sampling method, meaning that data collection was carried out by selecting research samples based on certain criteria and considerations. This study measures the level of influence of the choice variable on tax avoidance which is the dependent variable. Transfer pricing and earnings management are independent variables in this study